Kombinasi Minyak Kayu Putih dan Jeruk Nipis terhadap Mortalitas Pediculus humanus capitis - Janatin Nur Aripin; Dita Pratiwi Kusuma Wardani; M Luthfi Almanfaluthi; Isna Hikmawati (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2022)
The use of synthetic chemical pediculicides is known to have side effects and the occurrence of resistance so plant-based pediculicides are needed to kill Ph. capitis. Eucalyptus and lime oil are known to have an effect in killing Ph. capitis. The purpose of this study was to determine the effectiveness of the combination of eucalyptus and lime oil on the mortality of Ph. capitis. This study was conducted in a true experimental with a post-test-only control group design in May 2021. This study consisted of 5 treatment groups, one group as a positive control (permethrin 1%), one group as a negative control (aquadest), and 3 groups received treatment with a combination of eucalyptus and lime oil in the proportions of 1:3 (25 ml of eucalyptus oil: 75 ml of lime juice), 1:1 (50 ml of eucalyptus oil: 50 ml of lime juice) and 3: 1 (75 ml eucalyptus oil: 25 ml lime juice). It was repeated 3 times so that the total sample was 150 Ph. capitis which was observed every 5 minutes for 1 hour. The research data were analyzed using the Kruskal-Wallis test and continued with the Posthoc Mann-Whitney U test. Mortality of Ph. capitis in the combination group the most effective was the combination of 75% eucalyptus oil and 25% lime oil in the 5th-minute observation of 100% mortality compared to the control group and other groups.